The Lewis & Clark Expedition - Domnauer, Teresa (New York : Children's Press, 2013)
Presents an introduction to the Lewis and Clark Expedition, providing information on the Louisiana Purchase and their travels westward to Oregon from 1804 to 1806.
Setting the scene : the uncharted West -- Preparing for the expedition -- The Missouri River -- Crossing the Rockies -- The journey home -- Map of the events : what happened where? -- The story continues : westward expansion -- Influential individuals -- Timeline -- Living history -- Resources -- Glossary.
Includes bibliographical references (p. 61) and index.
6.5
3-6
Keywords: Lewis and Clark Expedition (1804-1806); West (U.S.) -- Discovery and exploration -- Juvenile literature; West (U.S.) -- Description and travel -- Juvenile literature; West (U.S.) -- Discovery and exploration; West (U.S.) -- Description and travel; West (U.S.) -- Exploration; West (U.S.) -- Description and travel; West (U.S.) -- Discovery and exploration; West (U.S.) -- Description and travel